The drag effects of energy-water constraints on China’s economic growth under carbon mitigation goals - Yu, Xinxin; Chen, Yifan; Jiang, Mingdong; Zhong, Guanyu; Xu, Heyichen; Shen, Xiaomei; Kong, Qianhui (Frontiers in Earth Science, 2023)
Energy and water resources function as the base for humans’ socioeconomic development, which are closely linked with each other in the production process. With the rapid economic development, the contradiction between the supply and demand of energy and water resources has become acute. Meanwhile, the carbon reduction goals further enhanced the energy and water constraints, which inevitably have a significant impact on economic growth. Exploring the effect of energy and water constraints on the economic growth under climate goals is essential for policy maker to minimize the economic loss during carbon control. To realize this aim, we introduced the modified Romers’ economic growth model to estimate the impact of energy-water constraints on economic growth based on relative data in 30 provinces in China from 2000 to 2019. Then the spatial-temporal characteristics of the energy-water drag effects on China’s economic growth have been analyzed. We further applied scenario analysis method to investigate the changes in growth drag effects of energy and water resources under carbon mitigation goals in 2025 and 2030. The results show that China’s economic growth rate was reduced by 7.72% and 7.99% during the study period due to energy and water resources constraints respectively. In terms of the temporal trend, the energy-water growth drag effect shows a downward trend as a whole during 2000–2019, and the growth drag of energy on economic growth is slightly greater than that of water resources. As to spatial distribution, regions with high constraint effects of energy and water on economic growth are mainly located in the East China, while some north regions feature low energy-water constraints. According to the simulation results, China’s energy-water drag effects on the economic growth are 6.85% and 7.03% respectively, under the baseline and strong carbon control scenarios, higher than the 6.53% under the weak carbon control. Based on this, this paper proposes to design targeted energy-water constraint strategies and promote production efficiency to achieve a win-win situation of economic development and dual-carbon goals.